Acetabular Revision in THA Using Tantalum Augments Combined with Impaction Bone Grafting. Issue 4 (July 2013) - Gehrke, Thorsten; Bangert, Yannic; Schwantes, Bernd; Gebauer, Matthias; Kendoff, Daniel
Introduction: Acetabular revision with associated bone loss in uncontained defects can be difficult. We report preliminary results utilising a novel technique, combining tantalum-augments with allograft bone and cemented cups. Patients and methods: Forty-six patients undergoing cup revision with a tantalum augment and allografting were clinically (HHS) and radiographically reviewed at an average of 46 months postoperatively. There were 28 type-2B and 18 type-3A Paprosky defects. Postoperative images were assessed for osteointegration, bone-remodelling and recreation of the native hip centre. Results: The average patient age at time of acetabular revision was 65 years, with 18 male and 28 female patients. The HHS improved on average from 44 to 82 points. Correction of the high hip centre was possible in all patients with average medialisation of 10 mm and lowering of the hip centre by 14 mm. Four patients (four hips) sustained a hip dislocation postoperatively and one required revision. Two acetabular revisions were necessary after implantation, because of early cup loosening and failure of the construct. In one of these, the tantalum augment was found to be well fixed. Of the remaining hips, at latest radiographic follow-up, 44 tantalum implants were radiographically stable and osteointegrated. Non-progressive radiolucent lines were present around the acetabular component in two other hips. Conclusion: The combination of tantalum-augmentation with impaction allografting is a promising technique to manage severe uncontained acetabular defects.